INFLUENCE OF TYPE NUT TYPE, MANUFACTURE PROCESS AND TYPE OF INOKULUM ON CHANGE OF NUTRITION IN NUT TEMPE FERMENTATION OF TOLO BEAN - Nani Ratnaningsih; Mutiara Nugraheni; Fitri Rahmawati (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2009)
The objective of research is to increase pulses-based food security by the way of local foodstuff diversification, that is tempe from tolo bean. Specific objective of research is to study of influence some tolo bean types, making process, and inoculum types to nutrient changing during fermentation tempe from tolo bean.Research was done experimentally since May up to November 2008. Research was conducted by analysis proximate and digestible protein. Proximate analysis include water content, ash content, crude fat content, total protein content, dietary fibre content and carbohidrate content (by difference). Design research was complete block design with 2 times experiment replicates and 3 times sample replicate. Independent variable was tempe from tolo bean. Dependent variable was result of proximate analysis and digestible protein. Data analysis was conducted by analysis of variance and post hoc test of DMRT (Duncan Multiple Range Test) at 5 % significance level.Based on result of research can concluded that 1) process of tempe from tolo bean yielding which highest digestible protein was wet grind processing with usar leaf, and 2) tolo bean types, making process, and inoculum types had significantly influence to nutrient changing during fermentation tempe from tolo bean.